1983
DOI: 10.1037/0022-0167.30.2.227
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of verbal behavior and judgments of satisfaction in the supervision interview.

Abstract: This study investigated the relationship between verbal patterns of behavior and supervisor and trainee judgments of satisfaction in the supervision interview. Blumberg's Interactional Analysis System was used to code the interviews and a sequential analysis methodology was employed to characterize interactional patterns. Three independent areas of satisfaction were assessed: (a) supervisor's (or trainee's) evaluation of other; (b) supervisor's (or trainee's) evaluation of self; and (c) supervisor's (or traine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
86
1

Year Published

1987
1987
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(93 citation statements)
references
References 20 publications
(19 reference statements)
6
86
1
Order By: Relevance
“…In studies using Holloway's modified BlA, interrater reliability reports range from r = .72 to .81 (Granello et al, 1997;Holloway, 1982;Holloway & Wampold, 1983;Holloway & Wolleat, 1981). In the current study.…”
Section: Methodsmentioning
confidence: 94%
“…In studies using Holloway's modified BlA, interrater reliability reports range from r = .72 to .81 (Granello et al, 1997;Holloway, 1982;Holloway & Wampold, 1983;Holloway & Wolleat, 1981). In the current study.…”
Section: Methodsmentioning
confidence: 94%
“…Some existing tools evaluate a specific encounter [51,52,58,61,71], and others a sum of experiences [57,59,60,6270], although this may not be explicit. ExPRESS is the only instrument divided into two sections to assess both a specific encounter and a sum experience of supervision.…”
Section: Discussionmentioning
confidence: 99%
“…D. H. Granello and Hazler (1998) used a developmental model of cognitive complexity to propose an order to the counseling curriculum that exposes students to more and more cognttively advanced experiences. Holloway and Wampold (1983) found that counselor trainees with higher levels of cognitive complexity were more effective in generating appropriate clinical hypotheses than those who were less cognitively developed. According to Stoppard and Miller's (1985) review of the research, counselors with higher levels of cognitive complexity were more flexible in their counseling methods, more empathetic in their communication, more autonomous, and less prejudiced than those at lower levels of complexity.…”
mentioning
confidence: 96%